Accountability through dialogue: the Presidencîa Aberta e Inclusiva in Mozambique - Julia Leininger (Deutsches Institut für Entwicklungspolitik (DIE), 2011)
Accountability is a central feature of democracy. Governments must explain what they are doing, justify why they are doing certain things and not others. Moreover, accountability increases the likelihood of the improvement of public services if citizens have the political scope to hold politicians and administrators accountable, and potentially sanction them. Consequently, developing countries as well as the OECD-donor community have committed themselves to working towards the improvement of domestic accountability in developing countries. In many developing countries, ccountability is exercised through both formal and informal institutions. This paper summarises the results of an empirical study on accountability in Mozambique. It focuses on the Presidência Aberta e Inclusiva (PAI, Open and Inclusive Presidency), a legally not codified institution for accountability introduced by President Armando E. Guebuza. It provides a public forum for the president to engage in a dialogue with the population and the local administrations, in combination with an ongoing process of decentralisation. This study shows that the interaction between formal and more informal institutions has a mixed influence on policymaking and democracy. Overall, there is an untapped potential to improve the PAI as an institution for accountability that strengthens formal institutions. In analysing the interplay between the PAI and formal institutions in two Mozambican provinces, we assess it to be a relatively effective monitoring instrument. The PAI fosters a top-down logic of coherence and implementation of development policies at all state levels. In doing so, it particularly contributes to aligning development policies to the government's strategic five-year plan. The PAI has the potential to enhance the quality of democracy, as it offers the opportunity for the provision of accountability by different levels of the executive and a new venue for citizen participation in an environment in which other forms of participation are largely constrained. However, thus far, this potential for accountability and participation has not yet fully unfolded, because the process is dominated by the executive in processes of political decision making. The PAI creates a structure with challenging consequences for a coherent planning and implementation process at the sub-national level. It potentially poses a threat to the development of effective independent institutions at the local level, such as district administrations, municipalities and Conselhos Consultivos (consultative councils) that are actually tasked with ensuring a coherent implementation of development policies. The PAI's contribution to the Mozambican decentralisation process can be improved by raising awareness on the functions and responsibilities of formal institutions at the sub-national level and by more closely aligning the PAI's follow-up process to already existing policy processes. For donors it is not recommended to directly interact with the PAI in development aid, but to focus on its effect on existing development programmes.
Keywords: 330